Comparative Study between Pars Plana Vitrectomy with Internal Limiting Membrane Peel and Pars Plana Vitrectomy with Internal Limiting Membrane Flap Technique for Management of Traumatic Full Thickness Macular Holes - Hammouda Hamdy Ghoraba; Mahmoud Leila; Hashem Ghoraba; Mohamed Amin Heikal; Emad Eldin Mohamed Elgemai (Journal of Ophthalmology)
Purpose. To compare the efficacy of PPV and ILM peel versus PPV and IFT in patients with traumatic FTMH. Methods. Retrospective interventional comparative case series including two groups of patients with traumatic FTMH. Patients were divided into group I (ILM peel) and group II (IFT). The main outcome measure was closure of the macular hole and restoration of the foveal microstructure. The independent-samples T-test and ANOVA test were used to study the mean between 2 groups and calculate the P value, whereas the bivariate correlation procedure studied the interaction between the variables tested. Results. Group I included 28 patients. Mean preoperative MLD was 757 µm. Mean preoperative BCVA was approximately 20/320. Group II included 12 patients. Mean preoperative MLD was 529.5 µm. Mean preoperative BCVA was 20/320. Group I had a macular hole closure rate of 75% versus 92% in group II P=0.05. Mean BCVA improvement was 2.5 lines in group I versus 5 lines in group II P=0.02. Disrupted ELM and IS/OS was the most salient finding in both groups. Conclusion. IFT has a significantly superior anatomic and functional outcome compared to ILM peel in traumatic FTMH.